A common theme for axonopathies? The dependency cycle of local axon homeostasis. Issue 2 (18th March 2021) - Prokop, Andreas
Abstract: The number of acquired or inherited conditions leading to axon degeneration (from now on referred to as axonopathies) is vast. To diagnose patients, clinicians use a range of indicators including physiology, morphology, family and patient history, as well as genetics, with the specific location of the lesion within the nervous system being a prominent feature. For the neurobiologist, these criteria are often unsatisfactory, and key questions remain unanswered. For example, does it make sense that different axonopathies affect distinct neuron groups through distinct mechanisms? Would it not be more likely that there are common routes to axon degeneration? In this opinion piece, I shall pose this fundamental question and try to find answers that are hopefully thought‐provoking and trigger some conceptual rethinking in the field. I will conclude by describing the 'dependency cycle of axon homeostasis' as a new approach to make sense of the intricate connections of axon biology and physiology, also suggesting that different axonopathies might share common paths to axon degeneration.